Genotype-Guided Use of P2Y12 Inhibitors: A Review of Current State of the Art - Al-abcha, Abdullah; Radwan, Yasser; Blais, Danielle; Mazzaferri, Ernest L.; Boudoulas, Konstantinos Dean; Essa, Essa M.; Gumina, Richard J. (Frontiers in Cardiovascular Medicine, 2022)
The pharmacodynamics of the purinergic receptor type Y, subtype 12 (P2Y12) inhibitors has evolved. Our understanding of the metabolism of P2Y12 inhibitors has revealed polymorphisms that impact drug metabolism and antiplatelet efficacy, leading to genetic testing guided therapy. In addition, assays of platelet function and biochemistry have provided insight into our understanding of the efficacy of “anti-platelet” therapy, identifying patients with high or low platelet reactivity on P2Y12 therapy. Despite the data, the implementation of these testing modalities has not gained mainstream adoption across hospital systems. Given differences in potency between the three clinically available P2Y12 inhibitors, the increased bleeding risks of a large proportion of patients on P2Y12 inhibitors, the balance between thrombotic and bleeding risks must also be carefully considered. Here we review the current data for genetic and functional testing, risk assessment strategies, and guidelines for P2Y12 inhibitors guided therapy.